Double-Door or "French-Door" Cervical Laminoplasty. Issue 9 (November 2015) - Unknown
Abstract : Purpose: Cervical spondylotic myelopathy (CSM) is a condition resulting from cervical stenosis. Manifestations of CSM include paresthesia in the extremities, loss of fine motor skills, balance problems, and bowel and bladder dysfunction in advanced disease. Laminoplasty is one surgical treatment option. The goal of laminoplasty is to reposition the laminae to expand the spinal canal, allowing the spinal cord to migrate posteriorly. There are various laminoplasty techniques; the main ones being open-door laminoplasty and double-door laminoplasty. This manuscript demonstrates a double-door laminoplasty otherwise known as a "French-door" laminoplasty discusses the indications and outcomes of this procedure. Methods: The double-door laminoplasty creates an opening in the midline of the spinous processes and a symmetrical expansion with hinges on both laminae. Bilateral troughs are drilled on each laminae using a bur, and opened liked a French-door, allowing the spinal cord to move posteriorly in the enlarged spinal canal. The space between the gapped laminae are then stabilized by allograft. Results: This manuscript presents the case of a 56-year-old man with CSM caused by multilevel cervical stenosis. The patient had classic signs and symptoms of CSM including problems with fine motor skills and walking difficulty. The video demonstrates the spinal cord decompression achieved with the French-door technique from C4 to C6 with a dome laminectomy at C3. Conclusions: There are many surgical treatments for cervical stenosis including anterior cervical discectomy and fusions and posterior procedures such as laminoplasty or laminectomy and fusion. The indications and technical pearls for French-door laminoplasty are presented as an effective option for the treatment of multilevel cervical stenosis.